PREVALENCE, OUTCOME AND RISK FACTORS ASSOCIATED WITH CONGENITAL MALFORMATIONS IN NEONATES AT A TERTIARY CARE HOSPITAL -A RETROSPECTIVE STUDY: http://doi.org/10.46536/jpumhs/2023/13.01.389 - Shaista Ehsan1 , Nadia Shahid2 , Mahreen Ahsan3 , Asif Nadeem Jamali4 , Habibullah Siyal5 , Aliza Aman6 , Sundas Parveen7 ., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT INTRODUCTION: There is a high burden of congenital anomalies worldwide and more so in the developing countries. These birth defects contribute significantly to the neonatal mortality rate in our country, which is one of the highest globally. Addressing and identifying the risk factors for these conditions is imperative for their prevention .OBJECTIVE: this study was done to determine the prevalence of congenital malformations and the risk factors associated with them. METHODOLOGY: this cross-sectional retrospective study was carried out at the Pediatric unit of Ziauddin Hospital from 1st January 2020 till 1st January 2023.Data was extracted from the electronic health records and entered on a pre-designed proforma. Information regarding maternal risk factors , antenatal visits ,neonatal characteristics and type of congenital anomalies was noted .Data was analyzed using SPSS version 20 and expressed as frequencies and percentages and chi square test was applied with P-value of <0.05 considered statistically significant. RESULTS :The prevalence of congenital malformations was 4.5%.Anomalies related to the central nervous system were the highest ,followed by cardiac birth defects .A smaller percentage undertook regular antenatal visits and folic acid supplementation. Family history of birth defects is a significant risk factor. CONCLUSION: Congenital malformations are a frequent occurrence in our set up .Effective antenatal care and screening are the cornerstone of preventing these disorders.